Pengaruh profitabilitas, investment oppportunity set, tangibilitas, earnings volatility dan firm size terhadap struktur modal pada industri farmasi - SATRIYO WIBOWO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2016)
This research is to test and analyze empirically the influence of profitability, Investment Opportunity Set (IOS), tangibility, earning volatility, and firm size toward capital structure. It was studied again because previous studies were inconsistent with pecking order and trade-off theory. The object of this research is company in pharmacy industry that listed in Indonesia Stock Exchange period 2005-2013. Seven companies met the criteria and were analyzed using Eviews8 panel data regressions with fixed effect model to test the hypothesis. The result of this research shows that profitability and earning volatility influence capital structure, while Investment Opportunity Set (IOS), tangibility, and firm size do not influence capital structure.